Le secret professionnel inscrit dans la Charte des droits et libertés de la personne au Québec - Vallières, Nicole (Les Cahiers de droit, 1985)
Professional secrecy is expressly defined in section 9 of the Québec Charter of Human Rights and Freedoms. Hence, the substance of this section acquires major importance and an analysis of it must precede any other procedure. Professional secrecy as described therein is a right vested in the person and as such, is an obligation that all professionals governed by the law must respect. This right originates in the professional relationship and only concerns the confidential content of information disclosed at that time. Lastly, the professional's duty to discretion may be suspended by a specific statutory provision without there being an express need to derogate therefrom in the Charter of Rights.